2022
DOI: 10.1101/2022.02.02.22270309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Longitudinal Aging Study Amsterdam COVID-19 exposure index: a cross-sectional analysis of the impact of the pandemic on daily functioning of older adults

Abstract: ObjectivesThe aim of this study was to develop an index to measure older adults’ exposure to the COVID-19 pandemic, and to study its association with various domains of functioning.DesignCross-sectional study.SettingThe Longitudinal Aging Study Amsterdam (LASA), a cohort study in the Netherlands.ParticipantsCommunity dwelling older adults aged 62-102 years (n=1089) who participated in the LASA COVID-19 study (June-September 2020), just after the first wave of the pandemic.Primary outcome measuresA 35-item COVI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This study provides novel evidence on the influence of COVID-19 lockdowns on individual and social activities in older adults, and how these negatively impacted the mental health of community-dwelling older people in Indonesia. Older adults represent a population group at very high risk of adverse mental health outcomes due to social isolation, particularly during the lockdown periods during the COVID-19 pandemic [ 25 , 56 ]. However, very little research has focused on the effect of COVID-19 lockdowns on older adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study provides novel evidence on the influence of COVID-19 lockdowns on individual and social activities in older adults, and how these negatively impacted the mental health of community-dwelling older people in Indonesia. Older adults represent a population group at very high risk of adverse mental health outcomes due to social isolation, particularly during the lockdown periods during the COVID-19 pandemic [ 25 , 56 ]. However, very little research has focused on the effect of COVID-19 lockdowns on older adults.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the USA, older adults (>65 years) comprise 80% of all COVID-19-related deaths and 31% of COVID-19 infections, despite comprising 17% of the total population [ 20 , 24 ]. Moreover, the COVID-19 pandemic is uncovering the vulnerability of older adults, especially during national mandatory lockdown periods [ 25 , 26 ]. In high-income countries, recent research has revealed that older adults showed poorer mental health (anxiety and depression symptoms), reduced social functioning (increased isolation) and lower physical functioning compared with pre-pandemic levels [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the USA, older adults (>65 years) comprise 80% of all COVID-19-related deaths and 31% of COVID-19 infections, despite comprising 17% of the total population [19,21]. Moreover, the Covid-19 pandemic is uncovering the vulnerability of older adults, especially during national mandatory lockdown periods [22,23]. In high-income countries, recent research has revealed that older adults showed poorer mental health (anxiety and depression symptoms), reduced social functioning (increased isolation) and lower physical functioning compared with pre-pandemic levels [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Covid-19 pandemic is uncovering the vulnerability of older adults, especially during national mandatory lockdown periods [22,23]. In high-income countries, recent research has revealed that older adults showed poorer mental health (anxiety and depression symptoms), reduced social functioning (increased isolation) and lower physical functioning compared with pre-pandemic levels [22]. Other studies have also reported that COVID-19 has caused them poor psychological health and well-being [24,25], fear of death, worry [24], stress [26], feeling of loneliness [27][28][29] and sleep disturbances which also led to increased depression [24,27].…”
Section: Introductionmentioning
confidence: 99%